Microeconometric Analyses of Cognitive Achievement Production - Bernhard Enzi (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2017)
This volume was prepared by Bernhard Enzi while he was working at the ifo Institute. It was completed in 2016 and accepted as a doctoral thesis by the Department of Economics at the University of Munich. It includes an introduction and four self-contained chapters that focus on the economics of education. Chapter 1 gives a short introduction into the topic and lays out some general aspects about the methodological frameworks used in this volume. Chapter 2 is focused on the effect of pre-service cognitive and pedagogical teacher skills on student achievement. Methodologically, the chapter uses micro data from the German National Educational Panel Study and estimates parameters of a value-added model of cognitive achievement. Chapter 3 further investigates a battery of other potential determinants of teacher quality. Chapter 4 analyses predictors of gender differentials in test scores and teacher assessments. Finally, using data from the German Centre for Research on Higher Education and Science Studies, chapter 5 investigates the effects of the Bologna-Reform on student outcomes based on an instrumental variables approach. – – Die vorliegende Arbeit wurde von Bernhard Enzi während seiner Tätigkeit am ifo Institut verfasst. Sie wurde 2016 abgeschlossen und von der volkswirtschaftlichen Fakultät der Universität München als Dissertation angenommen. Die Arbeit besteht aus einer Einführung und vier eigenständigen Kapiteln zur Bildungsökonomik. Kapitel 1 gibt eine kurze Einführung in das Thema und erläutert einige methodische Aspekte, welche in den übrigen Kapiteln Anwendung finden. In Kapitel 2 wird der Zusammenhang von kognitiven und pädagogischen Leistungen von Lehrern mit den Ergebnissen ihrer Schüler in standardisierten Tests untersucht. Hierzu werden Daten aus der National Educational Panel Study genutzt um die Parameter eines Value-Added-Modells zu schätzen. In Kapitel 3 wird eine Reihe weiterer potentieller Determinanten von Lehrerqualität untersucht. Kapitel 4 betrachtet Prädiktoren von Geschlechtsunterschieden in Schülerleistungen und Lehrerbewertungen. Schließlich werden in Kapitel 5 die Effekte der Bologna-Reform auf verschiedene Dimensionen von Studentenleistungen analysiert. Auf Grundlagen von Daten des Deutschen Zentrums für Hochschul- und Wissenschaftsforschung wird der kausale Einfluss der Reform mit Hilfe eines Instrumentenvariablenansatzes geschätzt.
Keywords: 330